Efficacy of antimicrobial photodynamic therapy as an adjuvant in periodontal treatment in Down syndrome patients. Issue 9 (December 2016) - Martins, Fabiana; Simões, Alyne; Oliveira, Marcio; Luiz, Ana; Gallottini, Marina; Pannuti, Claudio
Abstract Down syndrome (DS) has characteristics that include mental retardation, a characteristic phenotype, congenital heart defects, immune disorders, and increased risk of periodontal disease (PD). Antimicrobial photodynamic therapy (aPDT) is the combined use of photosensitizers associated with low-level laser (LLL) and oxygen, leading to singlet oxygen formation, which contributes to the antibacterial activity of the phagocytes, killing bacteria. The objective of this study was to evaluate the efficacy of aPDT as an adjuvant to conventional periodontal treatment of PD in DS patients. A double-blinded, controlled, randomized, split-mouth study was conducted. A total of 13 DS subjects who were 18 years or older and who presented at least one tooth in each quadrant of the mouth with probing pocket depth (PPD) equal to or greater than 5 mm were included. The patients were evaluated at three different times: at the baseline, PPD were obtained. After 1 week, conventional scaling and root planing (SRP) was performed, and two randomly selected quadrants also received aPDT. One month after SRP, all the patients were reevaluated. Periodontal conditions were improved among all the participants. The PDT-with-SRP group presented a nonsignificant reduction in PPD (mean = 1.27 mm, median = 1.17 mm) relative to that of the SRP group (mean = 1.00 mm, median = 0.95 mm). Changes over time were compared using the Wilcoxon test. A significant reduction in median PPD was observed in both groups (p  = 0.001). Both types of periodontal treatment, with and without PDT, were similarly effective and were associated with good clinical response.